Międzyformacyjne cechy demokracji politycznej: [Inter-formal features of political democracy] (Studia Prawnicze / The Legal Studies, 1981)
This article discusses the relation between moral and political unity of the nation and the variety of attitudes and opinions which may and should be displayed within the scope of such unity. The notion of moral and political unit of the nation contained in the exposé of Polit-Bureau presented during the Congress of the PUWP is the starting point of these considerations.The Author discusses separately political and moral unity of the society.Political unity of the Polish nation plays the role of a structural principle which sets the limits of lawful political activity in the legal system of the PPR.Political opponents of socialism who lead public anti-socialist activity cannot fully benefit from the constitutional political freedoms. However, they make use of their electoral, social and economic rights, and the rights which guarantee their personal freedom and the rule of law.For political unity of the nation acceptance of fundamental principles and values constituting this unity is of utmost importance; less important are justi- fications and motivations of such acceptance (which may be based on various ideological or etical premises).Divergences of opinions and controversies displayed within the scope of political unity of the nation may concern operative aims of socialist state policy and the means of its realization. They may also concern other issues of utmost importance (such as e.g. methods of realization of the leading role of the Party and fundamental priorities in social and economic policy.).Public pronouncement of different opinions and attitudes (within ideological limits of political unity of the nation) should be allowed both before and after making political decision) as well as during the process of its realization). The requirement that the minority should submit to the decision of the majority concerns organized political actions and does not exclude the rights of persons of minority views to present in public opinions contrary to the position of the ma- jority and to the political decision made on this basis.Moral unity of the society consists in the fact that a decisive majority of the society accepts certain catalogue of values and principles of axiological character. The Author distinguishes here four basic categories of such values: 1) universal values of inter-formational character, acceptance of which in social practice is an elementary condition of existence of society and human race; 2) universal inter- formational values which are not necessary for the existence of human race; 3) values established and developed in capitalist formation; 4) values specific for socialist formation.Moral unity of the Polish nation in the period of building developed socialist society is based on universal acceptance of all the above mentioned categories of values and moral principles among which values specific for the socialist system play the leading role. Such acceptance is based on various motivations.The catalogue of values constituting moral unity of the Polish society is open and dynamic.There is a close relation between political and moral unity of the society.Elimination of antagonistic class structure of the society is the fundamental sociological promis of moral and political unity of the nation.Phenomena such as unjust social inequalities, violations of the rule of law by state aparatus, defective functioning of the mechanisms of socialist democracy, endanger moral and political unity of the Polish nation.